타우린 처리에 의한 나리 기내 식물체 생산체계 최적화 - 이상희(Sang-hee Lee); 양환래(Hwan-rae Yang); 김선태(Sun Tae Kim); 전태환(Tae Hwan Jun); 김용철(Yong Chul Kim); 김종보(Jong (Journal of plant biotechnology, 2017)
Lilies as cut flowers are one of the most popular ornamental plants in South Korea. It is necessary to develop lily cultivars with high qualities. Therefore, highly efficient propagation systems are needed following release of elite cultivars. In this study, we used taurine treatment to improve the growth conditions including shoot and bulb formation, fresh weight gain, and reduction of rooting and browning. We experimentally evaluated the effect of taurine as a growth stimulator, at concentrations of 0, 2.5, 5, 10, 15 and 20 mg/l. The results showed that 20 mg of taurine enhanced shoot formation by 85% and increased fresh weight 5.5-fold, which was higher than the approximately four-fold increase in the control. In addition, multiple bulb formation rate was increased by 80% and rooting by 82% following exposure to 20 mg/l of taurine. The efficiency of taurine treatment was higher than that of control with 50% multiple bulb formation rate and 60% rooting rate. The browning was 10.6% at 2.5 mg/l of taurine when compared with 0.8% at 20 mg/l. Taurine showed a positive effect on the overall growth of lily plants in terms of increased fresh weight, shoot formation rate, rooting, and formation of multiple bulbs, indicating that taurine can be used as an alternative to amino acids or as an antioxidant such as citrate and vitamin C in plant tissue culture. 나리는 절화용으로 대한민국에서 인기 있는 작물 중 하나로 고품질의 우수한 나리 품종이 개발되어야 한다. 이러한 우수 품종이 개발된 후에는 고효율의 번식체계가 확립되어야 한다. 본 연구는 타우린 처리에 의해서 신초 및 구근형성, 생체중 증가 및 발근율 향상 등의 생장촉진 효과와 갈변율 감소효과를 통한 나리 '레드플레임' 품종의 기내 식물체 생육 조건 체계 확립을 위해 수행되었다. 타우린이 생장촉진물질로 효능이 있는지 검증하기 위해 타우린을 0, 2.5, 5. 10, 15 및 20 mg/l을 첨가하였다. 그 결과, 타우린 20 mg/l 처리구에서 85 %의 신초형성률을 나타내었고 생체중은 5.5배 증가로 무처리구에서의 4.35배보다 더 높은 증가를 보였다. 구근형성 및 발근율 촉진 효과로는 타우린 20 mg/l에서 80%의 multiple 구근 형성률과 82%의 발근율을 나타내었다. 무처리구는 각각 50%의 multiple 구근 형성률과 60%의 발근율로 타우린을 첨가한 처리구의 효율이 더높았다. 또한 타우린 2.5 mg/l 처리구에서는 10.6%의 갈변율을 보인 반면에, 20 mg/l 처리구에서 0.8%의 갈변율을 보여 갈변율 감소에도 효과를 나타내었다. 타우린 처리구가 생체중 증가, 신초 생성률, 발근율 및 구근 형성 등의 전반적인 생장요인 들에 있어서 긍정적인 효과를 보여 줌으로써 나리를 포함하는 식물조직배양에서 타우린이 구연산 및 비타민 C와 같은 항산화제 또는 아미노산 대체제로서 사용 가능성을 보여 주었다.